Grief responses of Turkish families after the death of their children from cancer - (:unkn) unknown (TAYLOR & FRANCIS INC, 2006)
The aim of this qualitative study was to determine what the emotional reactions, experiences, and coping and support systems of families would be after the death of their children from cancer. The sample comprised 19 family members from five families. At the time of the interviews, it had been 8 - 14 months since the death of their children. The data were collected through in-depth interviews and analyzed through the content analysis method. Data were classified into three stages: shock and disbelief regarding the loss, sensitivity and inquiry into the past, and adapting to the loss. The first reactions of family members to either expected or unexpected losses were similar. All in the family displayed denial and disbelief, as well as self-directed aggressive behavior. All family members described the 3 - 4 months following the death of the child as very painful and distressing. Anger, blaming others and/ or themselves, depression, and anxiety were common feelings among all family members, appearing to be more prevalent in mothers. These emotions were accompanied by an inquiry into the past. At the time of the interviews, three fathers and all adolescent siblings had returned to their daily routines and developed new objectives. They were therefore considered to have adapted to the loss. It was seen, however, that all mothers remained in the sensitivity'' and inquiry into the past'' stages. It was found that families did not have effective social and professional support before or after their loss.
Keywords: PARENTAL BEREAVEMENT; CHILDHOOD-CANCER; DIAGNOSIS; MOTHERS